PENGARUH KOMPENSASI, MOTIVASI DAN KOMUNIKASI TERHADAP KEPUASAN KERJA KARYAWAN PADA LPD DESA ADAT BELAYU KECAMATAN MARGA KABUPATEN TABANAN - I GUSTI AYU META PURMINA DEWI (GANEC SWARA, 2024)
This research was conducted to determine the influence of Compensation, Motivation, and Communication on employee job satisfaction. The research object was the LPD (Village Credit Institution) of Belayu Customary Village, Marga District, Tabanan Regency. The sample consisted of 34 employees. The research method employed was quantitative using Multiple Linear Regression Analysis. The results of hypothesis testing, partially (t-test), showed a positive and significant influence of Compensation, Motivation, and Communication on employee job satisfaction at the LPD of Belayu Customary Village, Marga District, Tabanan Regency. The F-test results indicated that collectively, Compensation, Motivation, and Communication significantly influenced employee job satisfaction at the LPD of Belayu Customary Village, Marga District, Tabanan Regency